Sharing Remote Labs: A Case Study - Orduña, Pablo; Rodriguez-Gil, Luis; López-de-Ipiña, Diego; Garcia-Zubia, Javier (International Journal of Online and Biomedical Engineering (iJOE), 2013)
The interest on educational remote laboratories has increased, as have the technologies involved in their development and deployment. These laboratories enable students to use real equipment located in the university from the Internet. This way, students can extend their personal learning experience by testing with real equipment what they are studying at home, or performing hands-on-lab sessions at night, on weekends or whenever the traditional laboratories are physically closed. A unique feature of remote laboratories when compared to traditional laboratories is that the distance of the student is not an issue, so remote laboratories can be shared with other schools or universities. In this contribution, authors present and discuss a widely spread remote laboratory (VISIR, present in 6 european universities + 1 in India) shared among 3 institutions (2 universities + 1 high school).